ANALISIS PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA DEPOT AIR MINUM - Putra, Alex Pratama; Tarigan, Elsya Paskaria Loyda (Computer Science and Industrial Engineering, 2023)
Drinking water depots in Batam City are easy to find because there are in every residential area and an increase in competition is unavoidable. This study aims to determine the factors that influence purchasing decisions at drinking water depots in Batam City. The classical assumption test was carried out to test the regression model in order to obtain a regression model from the least squares method which produces an unbiased linear estimator. The use of multiple linear regression analysis was carried out to determine whether there is a relationship between the influence of product quality, price, location and promotion on purchasing decisions. Product quality variable with tcount 2.845 > ttable 2.06390 with a significant level of 0.009 <0.05 concluded that product quality has a positive and significant effect on the purchasing decision variable, then H1 is accepted. The location variable with tcount 2.663 > ttable 2.06390 with a significant level of 0.013 <0.05 concluded that location has a positive and significant effect on the purchasing decision variable, then H3 is accepted. The author suggests for drinking water depots in Batam City to maintain the quality of gallon refill water products, and choose strategic depot locations to increase profits.